Spelling - Allen, Robert (University Press, 2002)
A lively and practical guide to making spelling easy, this book will help you improve your spelling skills as well as understand the reasons for your spelling problems and how to deal with them. In two sections-one giving step-by-step guidance on how to help yourself, and the other a quick reference section-it is user-friendly and designed to make an often-forbidding subject readable. Illustrated: cartoons, boxes, 'dos' and 'don'ts', easy to follow sections Practical: how to work out spelling patterns, how words change because of grammar, double and single letters (eg disappoint, accommodation), words of foreign origin, using a dictionary effectively, using a spell-checker, and more Problem solving: knowing your spelling 'weaknesses', coping with confusables, debunking spelling myths, British and American English differences, capitalization Wordlists: boxes of confused spellings, as well as lists of word endings (eg -able or -ible, -acy or -asy) and noun and verb spellings, proper nouns, silent consonants